Strategies for vocabulary building: A dynamic approach to the acquisition of vocabulary in foreign language teaching - Allsopp, Jeanette (School of Languages, NIHERST, 1992)
This paper attempts to set out, in a theoretical framework, the need for vocabulary in the foreign language to be presented in a realistic manner calculated to gain the optimum result in relaying it to the student. It illustrates the static way in which vocabulary is still being taught in the secondary school, despite all the advances in foreign language pedagogical theory, and the ready availability of electronic and other aids. Eight strategies for the implementation of vocabulary acquisition are described: 1) the use of visuals, 2) role play, 3) oral portraiture, 4) the twinning of schools, 5) the project method, 6) the interview, 7) the random approach, and 8) computer assisted language learning
Keywords: Language education